1973
DOI: 10.1210/endo-92-5-1367
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Feedback Control of ACTH Secretion: Effect of Stress-Induced Corticosterone Secretion on Subsequent Stress Responses in the Rat1

Abstract: The stresses of electrical shock or laparotomy were repeated at various intervals up to 24 hr after the initial stress in an attempt to demonstrate inhibition of the second response as a consequence of corticosterone secreted after the first stress. In all cases the second response was equal to or greater in magnitude than the first. When the stress of prolonged (60-90 min) restraint was paired with the minor stress of injection several hr later, no inhibition of the corticosterone response to injection was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
92
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(106 citation statements)
references
References 11 publications
14
92
0
Order By: Relevance
“…A similar finding was noted for the males from Population Blood corticosterone levels have been shown to be significantly elevated during acute and chronic stress of rats and some other laboratory animals (Friedman & Ader, 1968;Ganjam, Campbell & Murphy, 1972;Zimmerman, Smyrl & Critchlow, 1972;Cook, Kendall, Greer & Kramer, 1973;Dallman & Jones, 1973;Riegle, 1974;Barlow, Morrison & Sullivan, 1975), and an increase in plasma ACTH precedes the corticosterone elevation (Cook et al, 1973 (Terman, 1973b).…”
Section: Animalssupporting
confidence: 59%
“…A similar finding was noted for the males from Population Blood corticosterone levels have been shown to be significantly elevated during acute and chronic stress of rats and some other laboratory animals (Friedman & Ader, 1968;Ganjam, Campbell & Murphy, 1972;Zimmerman, Smyrl & Critchlow, 1972;Cook, Kendall, Greer & Kramer, 1973;Dallman & Jones, 1973;Riegle, 1974;Barlow, Morrison & Sullivan, 1975), and an increase in plasma ACTH precedes the corticosterone elevation (Cook et al, 1973 (Terman, 1973b).…”
Section: Animalssupporting
confidence: 59%
“…In animals exposed to restraint after repeated swim in Experiment 2, ACTH and corticosterone levels are similar to those of acutely restrained rats. Therefore, repeated swim rats exhibit facilitated HPA responses to novel since their HPA responses match those of acutely stressed rats, as defined by Dallman and Jones [8]. We have previously observed facilitation of HPA responses to restraint after repeated swim [19].…”
Section: Discussionmentioning
confidence: 84%
“…Studies in rats revealed both facilitated and inhibited HPA responses to hypoglycemia when a prior stressor was administered (28). Whether the response is facilitated or inhibited appears to depend on the intensity and the magnitude of the corticosterone response to the first stimulus (10).…”
Section: Discussionmentioning
confidence: 99%